1996
DOI: 10.1103/physrevb.54.14971
|View full text |Cite
|
Sign up to set email alerts
|

dx2y2symmetry and the pairing mechanism

Abstract: An important question is if the gap in the high temperature cuprates has Typeset using REVT E X 1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
108
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 13 publications
9
108
1
1
Order By: Relevance
“…Two special types of phonons have attracted attention: the Cu-O buckling mode, which is attractive in the d-wave channel, 2,69,70,71,72,73 and the Cu-O breathing mode, which is repulsive in the d-wave channel. 2,70,71,73 Typically, the absolute values of the pairing interactions in the B 1g ('d-wave') channel for both types of vibrations are smaller than 0.1 eV, in the A 1g ('s-wave') channel about 0.5-1 eV; for spin fluctuations, the corresponding numbers are in the d-wave channel 0.5-1 eV and in the s-wave channel 1-2 eV. 73 The total electronphonon coupling constant in the s-wave channel amounts to λ s ≈ 0.4 − 0.6, 73,74,75,76,77 and in the d-wave channel to λ d ≈ 0.3.…”
Section: Coupling To the Zone Boundary Half Breathing Optical Phononmentioning
confidence: 99%
“…Two special types of phonons have attracted attention: the Cu-O buckling mode, which is attractive in the d-wave channel, 2,69,70,71,72,73 and the Cu-O breathing mode, which is repulsive in the d-wave channel. 2,70,71,73 Typically, the absolute values of the pairing interactions in the B 1g ('d-wave') channel for both types of vibrations are smaller than 0.1 eV, in the A 1g ('s-wave') channel about 0.5-1 eV; for spin fluctuations, the corresponding numbers are in the d-wave channel 0.5-1 eV and in the s-wave channel 1-2 eV. 73 The total electronphonon coupling constant in the s-wave channel amounts to λ s ≈ 0.4 − 0.6, 73,74,75,76,77 and in the d-wave channel to λ d ≈ 0.3.…”
Section: Coupling To the Zone Boundary Half Breathing Optical Phononmentioning
confidence: 99%
“…For conventional isotropic superconductors, the momentum dependence of the electron-phonon coupling is rather irrelevant to pairing, as all modes contribute to the Cooper instability. However, this is not the case in unconventional (sign-changing) anisotropic superconductors [9][10][11]. While electron-phonon coupling at large momentum transfers that connects momentum points with different signs of the superconducting gap leads to a suppression of superconductivity, scattering that involves small momentum transfers always enhances superconducting pairing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent Fermi-liquid based treatments of the long-range components of the Coulomb interaction have shown that the e-ph coupling constant can be significantly enhanced at small momentum transfers due to the quasi-2D nature of transport in the cuprates and the breakdown of screening in the deeply underdoped samples. 23,[44][45][46][47][48] The enhanced coupling in the forward scattering direction can enhance pairing in a d-wave superconductor 49 and also affects the energy scale of the dispersion renormalization. 50 The modification of the e-ph vertex appears to be generic as studies examining the short-range components of the Coulomb interaction as captured by the Hubbard interaction find similar forward scattering enhancements of the eph vertex.…”
Section: Introductionmentioning
confidence: 99%